Sanksi Pidana Pelaku Penipuan Pada Situs Kencan Online Tinder - Gabrielle Delfiani (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
The rapid development of technology has made human life inseparable from activities on the internet and social media so that it will open up opportunities for crime. According to POLRI data in 2020 there were 937 cases that occurred on the internet with 473 cases of hate content and hate speech, followed by online fraud with 259 cases and pornographic content with 82 cases. The government then issued Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. The variety of social media makes cybercrime more likely to occur, one of which is fraud on the online dating application Tinder. This research uses a normative legal method in which research will be carried out by examining library materials or secondary data through literature studies that are relevant to the cases raised as well as the internet, journal articles and electronic media. The results of the study reveal that cases of fraud in online dating applications on Tinder are crimes committed via the internet and the legal rules are contained in article 378 of the Criminal Code (KUHP) and if fraud occurs in cyberspace or online then you can use article 51 paragraph (1) jo article 35 paragraph Law Number 19 of 2016 Concerning Information and Electronic Transactions (UU ITE).